ANALISIS MAKNA OBJEK TEMPAT DUDUK DALAM ANIMASI “LA DIPLOMATIE DE L’ECLIPSE” (2022) - Lawrence, Kezia; Grahita, Banung (Institut Seni Indonesia Padangpanjang, 2024)
La Diplomatie De L'eclipse (2022) is a short animation work done by five students from Ecole MoPA. In this animation, it was found that objects in the form of